The contingent advantage of photosymbiosis in coral evolution - Zhensheng Wei; Wolfgang Kiessling; Zhen Guo; Michael J. Benton; Lewei Su; Yuangeng Huang; Zhong-Qiang Chen (Proceedings of the National Academy of Sciences, 2026)
The ecological success of modern reef-building corals is rooted in photosymbiosis, yet its macroevolutionary benefit remains unclear. Analyzing the Phanerozoic record of inferred zooxanthellate (Z) and azooxanthellate (AZ) corals over geologic time scales using Bayesian methods, we identify a fundamental shift in diversification dynamics and their drivers across the Paleozoic–Mesozoic transition. Although Z corals dominate modern tropical reef ecosystems, their Paleozoic counterparts were outpaced by AZ forms and showed failed recoveries after the Late Devonian mass extinction. We found Z coral diversification was primarily driven by origination, whereas AZ diversification was controlled by extinction. Multivariate birth–death models reveal that Paleozoic coral diversification was governed by abiotic stressors like warming and anoxia, to which Z and AZ corals showed similar vulnerability. The rise of scleractinian corals in the Triassic marked a distinct macroevolutionary regime shift after which photosymbiosis spurred coral diversification. Positive correlations between temperature and Z coral extinction dominated the Paleozoic, while negative correlations prevailed in the Meso-Cenozoic. The long-term reversal of this relationship could be the reduced supersaturation of the oceans with respect to CaCO 3 due to the emergence of calcareous plankton in the Triassic. Our deep-time perspective demonstrates that the advantage of photosymbiosis is not intrinsic but contingent on the broader ecological and environmental context.